Using Marble Workshops Residues as an Alternative to Soft and Coarse Aggregates to Produce Concrete - Nasef, Hatem Mohammed; Elkut, Ayman H.; Safey, Mohammed Adnan; Mami, Mohammed Ahmed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
Using marble industry waste as an alternative to local aggregate in concrete has been studied. The study found that the mechanical properties of both coarse and fine marble aggregate were within acceptable limits. Furthermore, it was observed that concrete containing 50% coarse marble aggregate alongside blasting aggregate exhibited higher compressive strength compared to concrete made with local aggregate (blasting and quarrying). Similarly, concrete containing 30% fine marble waste aggregate showed higher compressive strength than normal concrete. Based on these findings, the use of marble industry waste as an alternative to local aggregate is recommended within the limitations specified in the research. However, this application should be implemented based on specific restrictions and specifications outlined in the study, as certain proportions of marble waste were used in the concrete mixes and evaluated through various tests.